MEDIASI KONFLIK PERAN DAN KEADILAN PROSEDURAL DALAM HUBUNGAN PENGUKURAN KINERJA DENGAN KINERJA MANAJERIAL - Basri, Yesi Mutia (UI Scholars Hub, 2013)
This study explores managerial behavioral responses associated with performance measurement system. Design of performance measurement system is investigated financial and non-financial measures related to the four perspectives of Balanced Scorecard (BSC). This paper examines whether a role conflict and procedural fairness affect the relationship between performance measure and managerial performance. Based on a sample of 67 managers of regional Bank in Pekanbaru, the results from a structural model tested using Partial Least Squares indicate a relationship between performance measurement system and managerial performance is mediated by a role of conflict. However, this study not supported that procedural fairness mediated relationship between performance measurement system and managerial performance. These results may have important theoretical and practical implications.